Ergometric studies of proteins: New insights into protein functionality in food systems. Issue 2 (October 2015) - Zhang, Zhuo; Maya Desdier, Luis E.; Scanlon, Martin G.
Abstract Proteins impart desirable quality attributes to many foods. Our understanding of the energetics of proteins in food is derived primarily from calorimetry, but newer technologies that very precisely measure a protein solution's density and ultrasonic velocity provide quantitative data on the protein's ergometric properties (thermodynamic parameters associated with measurements of work). This paper provides an overview of commercially available oscillatory technologies for measuring such work-dependent properties and their thermodynamic basis. Examples illustrating the utility of these properties for investigating protein transitions and ligand binding are highlighted. Implications for better understanding protein functionality in food systems are also considered.